PENGELOLAAN USAHA TANI JAHE PUTIH DI KELURAHAN SEMPAJA KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Siti Balkis, Syarifah Maryam, dan Novita Sugiarti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The objective of this research  was to know about total cost production, total revenue, and income of the white ginger farm in Sempaja Utara urban village, Samarinda Utara sub district of Samarinda.This research started on May until July 2014, with research location is in Sempaja Utara urban village, Samarinda Utara Sub District.  The method that used is census method.  The data needed by research are primary and secondary data.  Primary data is got by observation and interview with responder use questionnaire which have been compiled in line with research.  Meanwhile secondary data is got from bibliography study and institution information which is related to research implementation.  The results of this research shows that : Based on the survey result to 16 respondent obtained  white ginger  production to one season is 1.000 kg-1 ha-1 at the price of selling Rp 10.000,00 kg-1.   Average revenue farmers was Rp 13.416.666,67 respondent-1 and total income from white ginger farming was Rp 28.547.500,00 with average farm income was Rp 4.549.401,04 respondents-1 to one season.  Value of R/C ratio was 1,57 meaning that the cultivated white ginger farm is already profitable.